Ovariohysterectomy requires more post-operative analgesia than orchiectomy in dogs and cats - Quarterone, Carolina; Loureiro Luna, Stelio Pacca [UNESP]; Crosignani, Nadia [UNESP]; Oliveira, Flavia Augusta de; Lopes, Carlize; Maia Lima, Alfredo Feio da [UNESP]; Araujo Aguiar, Antonio Jose de [UNESP] (Canadian Vet Med Assoc, 2017)
The requirement for post-operative analgesia after ovariohysterectomy (OH) versus orchiectomy in dogs and cats was compared. Twelve male and 12 female cats and 12 male and 12 female dogs received meloxicam, 0.1 mg/kg body weight, PO, 2 h before surgery. Eleven female cats and 3 female dogs received rescue analgesia (P = 0.002). No male of either species required rescue analgesia. The number of cats receiving rescue analgesia was greater in females than in males (P < 0.0001). One should not rely solely on preoperative short-acting opioid and preemptive use of NSAIDs to control postoperative pain following OH, in dogs or cats. Postoperative pain after OH should be assessed for at least 2 h for cats and 4 h for dogs, using species-specific validated tools, to ensure proper postoperative pain diagnosis and management. Male dogs and cats subjected to orchiectomy required less postoperative analgesia intervention than female dogs and cats submitted to OH.